2010
DOI: 10.1590/s1415-790x2010000100013
|View full text |Cite
|
Sign up to set email alerts
|

O uso de vernizes fluoretados e a redução da incidência de cárie dentária em pré-escolares: uma revisão sistemática

Abstract: The objective of this systematic review was to evaluate whether there is conclusive evidence that the professional application of fluoride varnish decreases the incidence of dental caries in preschool children. We searched the BBO, LILACS, MEDLINE and Cochrane electronic databases to identify controlled clinical trials that evaluated the development of cavitated caries lesions in children up to six years of age. Two researchers performed a critical appraisal of the studies selected for inclusion. Five-hundred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 20 publications
0
19
0
1
Order By: Relevance
“…This is consistent with the findings of a systematic review conducted by Carvalho et al . [26] However, a preventive fraction of 44% and 30–63% was reported in primary and young permanent dentitions, respectively, in another systematic review conducted by Petersson et al . [27] Rozier reported an overall preventive effect of professionally applied topical fluoride agents in the range of 22–46% in young permanent teeth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with the findings of a systematic review conducted by Carvalho et al . [26] However, a preventive fraction of 44% and 30–63% was reported in primary and young permanent dentitions, respectively, in another systematic review conducted by Petersson et al . [27] Rozier reported an overall preventive effect of professionally applied topical fluoride agents in the range of 22–46% in young permanent teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoride varnishes have been described as the most convenient means of having preschoolers use professionally applied topical fluoride, based on the premise that they are easy to apply and well tolerated. [2627] In recent decades, the use of fluoride varnish is much more concentrated than any other sources of fluoride; the reason might be the thickness and rapid setting of fluoride varnish, which reduces the amount of fluoride ingested, its ease of application, higher fluoride concentration and the fluoride adherence to tooth structures. It is critical that dentists and health services planners be familiar with the true range of benefits that fluoride varnishes offer specifically toward the prevention of ECC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical evidence has shown that biannual application of fluoride varnishes is effective in the control of caries progression, with a preventive fraction of 30% compared with placebo or non-treatment 5,16,19,25 . The application of high concentrated NaF, as varnish, is able to promote a CaF 2 -like layer precipitation on enamel, which can serve as a mineral reservoir, releasing fluoride during the cariogenic challenges 22,24 .…”
Section: Introductionmentioning
confidence: 99%
“…[6] This is also true for Brazil, North America, China, Australia, and Korea, with the prevalence rates of 27, 60, 67, 80, and 83.3, respectively. [78910]…”
Section: Introductionmentioning
confidence: 99%